Efeitos da vildagliptina na função endotelial, rigidez arterial e na pressão arterial em pacientes com diabetes mellitus do tipo 2 e hipertensão arterial - Martin, Luciana Neves Cosenso (2017)
Several trials have shown that dipeptidyl peptidase-4 (DPP-4) inhibitors, used to treat patients with diabetes mellitus type 2 (T2DM), improve endothelial function. Objectives: The current study investigated the effects of vildagliptin, a DPP-4 inhibitor, compared to glibenclamide on endothelial function and arterial stiffness (AS) in patients with T2DM and hypertension (HT). Casuistics and Methods: This trial was a prospective randomized, open label, controlled by drug. Fifty patients aged over 35 years with T2DM and hypertension, without cardiovascular disease, were randomly allocated to treatment with vildagliptin (n=25) or glibenclamide (n=25). Both groups used metformin. A 24-h non-invasive ambulatory blood pressure monitoring and assessment of endothelial function were performed before and after 12 weeks of treatment. Endothelial function was evaluated by peripheral artery tonometry (Endo- PAT 2000), measuring the reactive hyperemia index (RHI) and arterial stiffness. AS was also evaluated by augmentation index (Aix@75), pulse wave velocity (PWV) and central systolic blood pressure (cSBP) parameters with a portable compact digital BP recorder Mobil-O-Graph® 24-hour PWA monitor. The primary study outcome was change in the RHI after vildagliptin vs. glibenclamide treatment. Results: There were no changes in RHI in the vildalgliptin group (before 2.348 ± 0.5868; after 2.2408 ± 0.6019, P = 0.742) or in the glibenclamide group (before 2.3636 ± 0.5163; after 2.3375 ± 0.4996, P = 0.950) and no difference between groups (P = 0.5479). There was no difference between vildagliptin and glibenclamide treatment in AIx@75 PAT (P = 0.696), in 24-hs: cSBP (P = 0.274) and in PWV (P = 0.324). Conclusions: Vildagliptin in patients with T2DM and HT did not change endothelial function and AS during 12 weeks. Thus, this drug has a neutral effect on vascular function, providing its effectiveness for the treatment of patients with cardiovascular disease.